2011
DOI: 10.1002/ijc.26126
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green enhanced near‐infrared laser treatment of murine mammary carcinoma

Abstract: It is well accepted that near-infrared (NIR) lasers are appropriate to ablate benign lesions and induce irreversible thermal injury in deeply seated blood vessels. At this wavelength, the laser light penetrates deep (3–5 mm) into the skin. However, many researchers have reported noticeable pain, extending from mild to severe, during and immediately following NIR laser treatment. Intravenous administration of an exogenous chromophore (indocyanine green, ICG, dye) can effectively convert NIR laser light into hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…82 It has been demonstrated that ICG promotes the absorption of NIR laser light delivered by a diode laser, inducing more thermal damage to solid tumors after laser irradiation compared to laser alone. 173,174 In addition, local hyperthermia …”
Section: Photothermal Therapysupporting
confidence: 44%
“…82 It has been demonstrated that ICG promotes the absorption of NIR laser light delivered by a diode laser, inducing more thermal damage to solid tumors after laser irradiation compared to laser alone. 173,174 In addition, local hyperthermia …”
Section: Photothermal Therapysupporting
confidence: 44%
“…Nevertheless, given the potential photothermal capabilities of ICG and preferential accumulation in the tumor, additional localized destruction of tumor cells may be achieved to further enhance the antitumor efficacy of PDT (40,41). Literature has shown that tumorbearing mice administered with ICG and stimulated by NIR laser light at 808 nm exhibited significant tissue necrosis upon histological evaluation, which gradually led to reduction of tumor volume when compared to control groups (42). Hence, LPICG delivery system irradiated by NIR laser light may even be able to achieve selective and targeted dual cytotoxic effects at the tumor site elicited via both PDT and photothermal therapy.…”
Section: Nir Irradiation-induced Temperature Effectsmentioning
confidence: 44%
“…With the irradiation of NIR, the tumor cells containing proper photothermal agents were killed due to high temperature resulted from photothermal effect. Photothermal agents such as organic compounds (indocyanine green [11], polyaniline nanoparticles [12], etc. ), noble metal nanomaterials (Au [13], Ag [14] and Pd [15], etc.…”
Section: Introductionmentioning
confidence: 46%